Dehydrogenation catalyst as well as preparation method and application thereof

By introducing sulfur modification and Pt metal clusters on the magnesium-aluminum mixed oxide support, the cost and activity problems caused by high platinum content of precious metals are solved, and an efficient, stable and resistant carbon deposit dehydrogenation catalyst is achieved, which is suitable for cycloalkane dehydrogenation reaction.

CN119680582AActive Publication Date: 2025-03-25CNOOC GAS & POWER GRP

Patent Information

Application Number
CN202411874422.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The high content of precious metal platinum in the existing cycloalkane dehydrogenation catalysts leads to high costs and reduced catalyst activity. The catalyst is prone to carbon accumulation under high temperature and high pressure conditions, and its stability is insufficient, which limits its application in industrial production.

Method used

A dehydrogenation catalyst with sulfur-modified magnesium-aluminum mixed oxide as the support and Pt metal cluster as the active center is designed. The dispersion and stability of platinum are improved through surface modification and impregnation methods, the particle size of nanoparticles is controlled, and the carbon deposit is reduced.

Benefits of technology

A catalyst with good Pt dispersion, high stability and resistance to carbon deposits is achieved, which improves the catalytic activity and selectivity of the cycloalkane dehydrogenation reaction, reduces the use of precious metals, and reduces the cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680582A_ABST
    Figure CN119680582A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to a dehydrogenation catalyst precursor, a dehydrogenation catalyst and a preparation method and application of the dehydrogenation catalyst precursor. According to the dehydrogenation catalyst precursor, a sulfur-modified magnesium-aluminum mixed oxide is used as a carrier, and a Pt metal cluster is used as an active center; wherein the carrier is a mixed-state metal oxide with a layered hydrotalcite structure, a spinel structure and a near-crystalline synergistic structure. A magnesium-aluminum mixed oxide can be prepared by introducing a precursor of alkali metal magnesium into an aluminum oxide precursor, a layered structure or a spinel structure similar to hydrotalcite can be formed by regulating and controlling the calcination temperature, and by combining carrier surface regulation and control modification, the capability of regulating and controlling the interaction between metal and a carrier can be improved, and the performance of the catalyst is improved. Therefore, the active center of the cluster is maintained, and the acid-base property of the surface of the carrier is effectively modulated, so that carbon deposit is reduced, and the activity and stability of the catalyst are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst technology, and in particular to a dehydrogenation catalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen is an ideal fuel for clean energy and can replace traditional hydrocarbon raw materials. Due to its high mass energy density of 141.6 MJ / kg, which is three times that of gasoline, it produces water as the only byproduct. The challenges faced by these applications are related to the difficulty of efficient hydrogen storage. Currently, most hydrogen storage is based on compression and liquefaction technology, which brings safety issues and low storage density, as well as transportation, evaporation losses and other high cost issues.

[0003] Dehydrogenation is a chemical reaction that can be used for hydrogen production, hydrogen storage, and to generate value-added unsaturated hydrides. Due to the bond breaking process, dehydrogenation reactions are generally endothermic and require high energy input to achieve sufficient reaction performance. Therefore, catalysts increase activity and reaction rate by lowering the activation energy barrier and control the reaction pathways on the catalyst surface to control product selectivity.

[0004] Liquid Organic Hydrogen Carrier (LOHC) is an attractive alternative to store hydrogen in the form of chemical bonds, which can solve many limitations of existing technologies. Reversible LOHC systems always consist of a pair of hydrogen-deficient and hydrogen-rich organic compounds that store hydrogen through hydrogenation and dehydrogenation, which has high potential for hydrogen storage and transportation applications. Cycloalkanes and aromatics with one or more six-membered rings are promising reversible LOHC systems. These stable alkane compounds have remarkably high storage capacity (between 6-7wt.% H2) and can be dehydrogenated / rehydrogenated under relatively low reaction conditions.

[0005] Supported metal catalysts are crucial for many processes in the chemical industry. The overall performance of these catalysts depends largely on the interactions of adsorbates at the atomic level, which can be manipulated and regulated by the different components of the active materials (i.e., support and active metal). Catalyst activity in heterogeneous (thermal) catalysis is described by regulating the metal-support interaction (MSI) through the relationship between the active component and the support to describe this complex phenomenon. The metal-support interaction in catalysis is affected by regulating the active particle size of metal oxides in different dimensions such as atoms, clusters and nanoparticles, thereby achieving the purpose of regulating their catalytic performance.

[0006] Metal-support catalyst is the most important catalyst model. Reasonable construction of MSI can effectively enhance catalytic performance. The strategies for regulating metal-support interaction are divided into three directions: (1) construction of support defects: support composition, support morphology, support doping, and surface modification; (2) properties of loaded active metals: size effect and active composition; (3) preparation and treatment methods: heat treatment, reducing agent, redox cycle, coating deposition, and adsorbate treatment.

[0007] As an important design strategy for catalysts, the construction of defect structures is the core of defect construction and preparation methods for different catalysts based on the physicochemical properties of catalysts, reaction evaluation and mechanism kinetics. Based on the causes of defect formation, crystal defects are divided into: thermal defects, impurity defects, non-stoichiometric defects, charge defects and irradiation defects: (1) Thermal defects, also known as intrinsic defects, are vacancies and / or interstitial protons generated by thermal fluctuations. The concentration of thermal defects is proportional to temperature. (2) Impurity defects, regarded as compositional defects, are defects caused by the introduction of external impurities. Therefore, the introduction of trace impurities will greatly change the physical properties of the crystal matrix. (3) Non-stoichiometric defects are caused by deviations from the law of chemical constant ratios, which are triggered by the exchange between the crystal matrix and certain components in the medium. (4) Charge defects involve defects in which the periodicity of the particle arrangement remains unchanged, but the periodic potential field is distorted due to the generation of electrons or holes. (5) The structural imperfections of catalysts produced under irradiation are called irradiation defects.

[0008] Supported platinum nanoparticle catalysts are industrially mature, high-quality heterogeneous catalysts used in hydrocarbon refineries. In the field of methylcyclohexane dehydrogenation, Chiyoda Corporation has developed a liquid organic hydrogen storage system for methylcyclohexane (MCH) dehydrogenation / toluene rehydrogenation based on a sulfided alumina-supported platinum catalyst (S-Pt / Al2O3), and demonstrated its feasibility and advantages in hydrogen storage and transportation. However, the high cost and low natural abundance of platinum limit its widespread application. Therefore, how to achieve efficient utilization while reducing the content of precious metal platinum is a path that technology needs to explore.

[0009] The catalytic technology for the dehydrogenation of methylcyclohexane faces some problems and shortcomings in current industrial applications, mainly including cost problems caused by high mass fraction of loaded platinum, aggregation and deactivation of active sites caused by weak metal-carrier interaction that cannot stably anchor platinum nanoparticles, carbon deposits on the catalyst surface during the reaction, and catalyst deactivation during long-term reactions. For example, cost problems caused by high content of precious metal platinum, for example, the platinum content in patent application CN 117899863 A is 18.02%, and the platinum content in patent application CN 116851023 A is 5% (particle size is 2 nanometers); although patent application CN118162160 A uses a strategy of preparing a loaded catalyst by modifying the γ-Al2O3 carrier with ammonium sulfate to reduce the platinum content, and obtains a catalyst with a platinum mass fraction of less than 1%, a large amount of hydrogen is co-fed in the 1 hour, 24 hour and 600 hour long period tests, and its hourly space velocity is relatively too slow (0.5 ml / min, 50 times the flow rate of 0.01 ml / min of methylcyclohexane). Patent application CN 113070061 A proposed to modify the Al2O3 carrier by doping lanthanide rare earth metals, and partially replace platinum with rhodium and ruthenium. Attempts to load precious metals in the range of 1% to 5% led to concerns about the cost in the industrialization process, and the reaction time of its dehydrogenation test was too short, only 40 minutes. Doping with base metals is also a common strategy in the field of catalysis. Patent application CN 109331823 A proposed to modify the magnesium aluminum hydrotalcite carrier by doping lanthanide cerium metal to load platinum, but did not give the mass fraction of the loaded platinum and the corresponding reaction time. Patent application CN 114011431 A proposed a strategy of doping nickel metal on γ-Al2O3-loaded platinum catalyst. Although this method has good conversion rate and selectivity in the laboratory tests described in it, the reactor and steel pipe materials used in the process of small and medium tests leading to industrialization contain nickel. In the actual reaction, the position where the catalyst contacts the reactor has an excessive nickel process, which leads to excessive cracking of methylcyclohexane and carbon deposition that blocks the reactor pipeline. Patent CN 107376907 B discloses a strategy for loading platinum on a tin-modified magnesium-aluminum hydrotalcite carrier. The platinum content in the patent is 0.5-5%, the reaction time is 10 hours, and the dehydrogenation conversion rate of methylcyclohexane in the best example is 98.5%. However, there are cost issues caused by the high platinum content and the lack of long-term stability testing.

[0010] In view of this, the present invention is proposed. Summary of the invention

[0011] In order to solve the cost and catalyst activity problems caused by the high content of precious metal platinum used in the catalytic technology of cycloalkane dehydrogenation reaction, the dehydrogenation catalytic activity deteriorates and the stability is difficult to maintain after reducing the platinum content loaded on the traditional alumina carrier. Specifically, in order to reduce the catalyst activity and selectivity, in the cycloalkane dehydrogenation reaction, the weak interaction between Pt metal and alumina carrier causes the catalyst to easily cause the Pt particles to continuously aggregate during long-term reaction, resulting in a decrease in catalyst activity. In addition, carbon deposition of the catalyst under high temperature and high pressure conditions is also an important reason affecting stability, which reduces its ability to work continuously for a long time. This lack of stability limits the application of the catalyst in industrial production. Therefore, the preparation strategy for designing the catalyst should consider aspects such as how to maintain the activity of the platinum site, how to control the particle size of the nanoparticles, and how to reduce carbon deposition.

[0012] In order to deal with the activity, stability and carbon deposition problems of the catalyst in the process of cycloalkane dehydrogenation reaction, the main goal of the present invention is to design a catalyst with good Pt dispersion, high stability and resistance to carbon deposition. Pt metal clusters (Clusters) are used as active centers, and alkaline magnesium-aluminum mixed oxides are used as catalytic carriers, and ammonium sulfate precursors are added to modify the surface, thereby anchoring Pt micro-nano clusters to prepare cycloalkane dehydrogenation catalysts with good dispersion and high stability. Pt is reduced from nanoparticles to nanoclusters, and its step sites are utilized, and through Pt-S-carrier anchoring sites, on sulfur-modified magnesium-aluminum mixed oxide carriers with synergistic structures (layered hydrotalcite structure, spinel structure, and synergistic structures of transitional mixed structures of the two), the catalytic efficiency and stability of Pt atoms can be maximized, while reducing the amount of precious metals used, achieving an effective method for reducing costs.

[0013] Based on this, the present invention provides a dehydrogenation catalyst and a preparation method and application thereof, which specifically include the following technical solutions: In a first aspect, the present invention provides a dehydrogenation catalyst, characterized in that the dehydrogenation catalyst uses a sulfur-modified magnesium-aluminum mixed oxide as a carrier and a Pt metal cluster as an active center; wherein the carrier is a mixed metal oxide having a layered hydrotalcite structure, a spinel structure, and a near-crystalline synergistic structure.

[0014] In the present invention, the near-crystalline structure refers to a transitional state that is not completely crystallized.

[0015] In the present invention, Pt metal clusters refer to dimensions between Pt single atoms and Pt nanoparticles, with active sites with higher index crystal planes than platinum nanoparticles, and are easier to prepare than single-atom platinum catalysts, so they are more suitable for industrial preparation and production and have higher stability. Clusters are multi-nuclear aggregates between atoms / molecules and macroscopic substances, with a definite atomic composition and chemical structure, representing the primary ecology of condensed matter, and are an ideal model for associating macroscopic properties and microscopic structures of substances, which is of great significance for a deep understanding and understanding of the laws of material transformation. Clusters and catalytic supports play a key role in the interaction between metal catalysts, and this interaction has a significant effect on the performance of catalytic reactions. Among them, cluster metal-support interaction is a unique interaction that occurs at the interface between metal nanoparticle clusters and metal oxide supports in solid-phase heterogeneous catalysts, which changes the electronic properties of the catalyst surface, thereby changing the catalytic process. Controlling cluster metal-support interactions in heterogeneous catalyst design provides many opportunities for the development of advanced catalysts with better catalytic performance.

[0016] The present invention found that the metal support interaction of Pt clusters and non-metallic sulfur modified magnesium aluminum mixed oxide catalysts in the cycloalkane dehydrogenation reaction has a significant effect on the catalytic performance: 1. The role of platinum clusters Highly active sites: Platinum clusters generally exhibit high catalytic activity due to their high surface energy and unique electronic structure. In the dehydrogenation reaction of cycloalkanes, platinum clusters can effectively activate hydrogen-hydrogen bonds and carbon-hydrogen bonds, thereby promoting the reaction.

[0017] Size effect: The size of platinum clusters has an important influence on their catalytic performance. Smaller platinum clusters are generally more active, but may also lead to stability issues for the catalyst. Optimizing the preparation method to achieve controllable cluster size and strong interaction with the support can balance catalytic activity and stability.

[0018] 2. Effect of sulfur-modified magnesium-aluminum mixed oxides Adjustment of acid-base properties: Sulfur modification of alkaline magnesium-aluminum mixed oxides can change the acid-base properties of the catalytic support surface. The introduction of sulfides can locally adjust the properties of the support surface, thereby affecting the dispersion and stability of metal clusters.

[0019] Enhanced metal dispersion: Sulfur-modified magnesium-aluminum mixed oxides as carriers help improve the dispersion of platinum clusters, reduce cluster aggregation, and thus improve the activity and selectivity of the catalyst.

[0020] 3. Influence of metal-support interactions Electronic effect: The introduction of sulfur substances will affect the electronic properties of the surface of the magnesium-aluminum mixed oxide support, thereby changing the microelectronic environment of the platinum clusters. This change can adjust the electron density of platinum and improve its catalytic activity. The mechanism of action of sulfides may be to affect the catalytic behavior of platinum on the support surface through electronic interaction with platinum.

[0021] Interface effect: The interface effect between platinum clusters and sulfur-modified magnesium-aluminum mixed oxide supports is crucial to catalytic performance. Sulfide modification may change the surface structure, active sites and interactions of the catalyst, affecting the rate and selectivity of the reaction. For example, sulfides can interact with the active sites of platinum and adjust its adsorption capacity for reactants.

[0022] Stability of reaction intermediates: The acid-base properties and electronic effects of surface-sulfurized magnesium-aluminum mixed oxides may affect the stability of reaction intermediates, thereby affecting the selectivity and product distribution of cycloalkane dehydrogenation reactions.

[0023] 4. Improvement of catalytic performance Activity and selectivity: Sulfur-modified magnesium-aluminum mixed oxides can improve the dispersion and stability of platinum clusters while tuning their electronic properties, which helps to improve the catalytic activity and selectivity of cycloalkane dehydrogenation reactions.

[0024] Stability: The stability of platinum clusters in the catalyst may be enhanced by modification with sulfur species, reducing the accumulation and deactivation of the catalyst during long-term operation.

[0025] Preferably, the particle size of the Pt metal clusters is 0.2-0.5 nm.

[0026] Preferably, the dehydrogenation catalyst is Mg modified with sulfur. x Al y O δ is a carrier, wherein x>y, δ represents any value between 4 and 6; more preferably, x:y=(2-3):1; further preferably, x:y=3:1.

[0027] Preferably, the surface area of ​​the carrier is 100 m 2 / g or more, pore volume is 0.50 cm 3 / g or more, and the pore diameter is 5nm or more.

[0028] Preferably, based on the mass of the dehydrogenation catalyst, the content of the platinum metal clusters is 0.1 wt% to 0.8 wt%.

[0029] In a second aspect, the present invention provides a method for preparing the dehydrogenation catalyst, comprising: S1: mixing a magnesium salt solution, an aluminum salt solution and a complexing agent to obtain a sol solution; S2: the sol solution is subjected to a gentle depressurization and heating operation in a rotary evaporator to obtain a gel, and then the gel is dried to obtain a solid precursor of a xerogel, and the precursor powder is obtained by grinding; S3: calcining the precursor powder in a muffle furnace at 300-400° C., and then calcining it in a tube furnace at 450-600° C. to obtain a carrier; S4: The support is loaded with a sulfur source and Pt clusters in sequence by an impregnation method.

[0030] In the present invention, by controlling the two calcinations, it is helpful to obtain a carrier having a layered hydrotalcite structure, a spinel structure and a synergistic structure in a crystalline state, wherein the layered hydrotalcite structure is a magnesium-aluminum layered oxide with a thickness of a single layer of magnesium ions and aluminum ions, and due to the excess of magnesium elements, cubic MgO is accumulated on the surface, and due to the second calcination of the carrier, magnesium-aluminum spinel and its transitional crystal form close to the crystal are also present in the carrier, and finally the above-mentioned special synergistic structure can be obtained.

[0031] Preferably, the magnesium salt comprises one or more of magnesium acetate, magnesium nitrate and magnesium chloride; And / or, the aluminum salt solution includes one or more of aluminum acetate, aluminum chloride and aluminum nitrate; and / or, the complexing agent comprises one or more of EDTA, citric acid, sodium citrate, ammonium citrate, maleic acid, glycine, ethanolamine, diethanolamine and triethanolamine; More preferably, the molar ratio of magnesium to aluminum in the magnesium salt solution and the aluminum salt solution is (2-3):1; And / or, the molar ratio of the complexing agent to the total metal ions of magnesium and aluminum is (4-9):1.

[0032] In the present invention, the solvent used to dissolve the magnesium salt, aluminum salt, sulfur salt and platinum salt may include one or more of ethanol, methanol, isopropanol, acetone and water, preferably deionized water.

[0033] The method for preparing the dehydrogenation catalyst is characterized in that: S1: mixing a magnesium salt solution, an aluminum salt solution and a complexing agent to obtain a sol solution; S2: The sol solution is subjected to a rotary evaporator at 40-90° C. to obtain a gel, and then the gel is dried at 80-100° C. to obtain a solid precursor of a dry gel, and the precursor powder is obtained by grinding; S3: calcining the precursor powder in a muffle furnace at 300-400° C. and then calcining it in a tube furnace at 450-600° C. to obtain a carrier; S4: impregnating the support in a sulfur salt solution, drying at 40-90° C. and 0.007-0.07 MPa, and then calcining at 300-400° C. to obtain a sulfur-modified support; S5: impregnating the sulfur-modified support in a platinum salt solution at 0.007-0.07 MPa, drying at 40-90° C., and then calcining at 300-400° C.

[0034] Preferably, the sulfur salt includes one or more of ammonium sulfate, ammonium sulfite, ammonium bisulfate, ammonium thiosulfate, and ammonium sulfite, and more preferably ammonium sulfate.

[0035] Preferably, the platinum salt includes one or more of chloroplatinic acid, ammonium chloroplatinate, platinum nitrate, platinum tetrachloride, platinum alkoxide, platinum oxide, platinum acetylacetone and platinum carbonyl compound, and more preferably chloroplatinic acid.

[0036] Preferably, in step S2, the sol solution is subjected to rotary evaporation at 40-90° C., with a rotation speed of 30-120 rpm, preferably 60 rpm. The water bath temperature is 40-90° C., preferably 60° C. The air pressure in the rotary evaporator is 0.007-0.07 MPa, preferably 0.02 MPa.

[0037] In a third aspect, the present invention provides use of a dehydrogenation catalyst in dehydrogenation of cycloalkane; preferably, the cycloalkane is methylcyclohexane.

[0038] Preferably, the dehydrogenation catalyst is pretreated before use, and the pretreatment comprises subjecting the dehydrogenation catalyst to a reduction reaction in a hydrogen atmosphere at 150-250° C., and then cooling to 25-30° C.; preferably, the hydrogen flow rate is 2-8 mL / min / gcat.

[0039] In the present invention, the freshly prepared dehydrogenation catalyst is in a stable oxidation state before use and needs to be reduced before use.

[0040] The dehydrogenation catalyst provided by the present invention and its preparation method and application can prepare a magnesium-aluminum mixed oxide by introducing an alkali metal magnesium precursor into an alumina precursor, and can form a hydrotalcite-like layered structure or a spinel-like structure or a mixed magnesium-aluminum oxide in a near-crystalline transition state by regulating the calcination temperature. Combined with the control and modification of the carrier surface, it helps to improve the ability to control the interaction between the metal carrier, which is beneficial to maintaining the cluster active center, and effectively regulates the acidity and alkalinity of the surface of the magnesium-aluminum mixed oxide carrier, thereby reducing carbon deposition and improving the stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 The dehydrogenation catalyst Pt-S / Mg3AlO provided in Example 1 of the present invention 4.5 Flow chart of the preparation of the vector.

[0043] Figure 2 The dehydrogenation catalyst Pt-S / Mg3AlO provided in Example 1 of the present invention 4.5 Preparation flow chart of .

[0044] Figure 3 The dehydrogenation catalyst Pt-S / Mg3AlO provided in Example 1 of the present invention 4.5 Transmission electron microscopy images before and after the reaction, where A represents before the reaction and B represents after the reaction.

[0045] Figure 4 The dehydrogenation catalyst Pt / Mg3AlO provided in Comparative Example 1 of the present invention 4.5 Transmission electron microscopy images before and after the reaction, where A represents before the reaction and B represents after the reaction.

[0046] Figure 5 The dehydrogenation catalyst Pt-S / Mg3AlO provided in Example 1 of the present invention 4.5 X-ray diffraction patterns before and after the reaction.

[0047] Figure 6 The dehydrogenation catalyst Pt / Mg3AlO provided in Comparative Example 1 of the present invention 4.5 X-ray diffraction patterns before and after the reaction.

[0048] Figure 7 The dehydrogenation catalyst Pt-S / Mg3AlO provided in Example 1 of the present invention 4.5 The dehydrogenation catalyst Pt / Mg3AlO provided in Comparative Example 1 4.5 X-ray photoelectron spectroscopy (XPS) of oxygen 1s orbital energy level diagram after dehydrogenation reaction.

[0049] Figure 8 The dehydrogenation catalyst Pt-S / Mg3AlO provided in Example 1 of the present invention 4.5 The dehydrogenation catalyst Pt / Mg3AlO provided in Comparative Example 1 4.5 Comparison chart of hydrogen programmed temperature reduction.

[0050] Fig. 9 The dehydrogenation catalyst Pt-S / Mg3AlO provided in Example 1 of the present invention 4.5 The dehydrogenation catalyst Pt / Mg3AlO provided in Comparative Example 1 4.5 Nitrogen isothermal adsorption-desorption curve (left) and pore size distribution diagram (right).

[0051] Fig.10 The dehydrogenation catalyst Pt-S / Mg3AlO provided in Example 1 of the present invention 4.5 The dehydrogenation catalyst Pt / Mg3AlO provided in Comparative Example 1 4.5 Thermogravimetric analysis diagram of .

[0052] Fig.11 The dehydrogenation catalyst Pt-S / Mg3AlO prepared in Example 1 of the present invention 4.5 Schematic diagram of programmed temperature pretreatment before the 300-hour long-cycle reaction test.

[0053] Fig.12 The dehydrogenation catalyst Pt-S / Mg3AlO prepared in Example 1 of the present invention 4.5 Schematic diagram of the programmed temperature reaction for the 300-hour long-cycle reaction test.

[0054] Fig.13 The dehydrogenation catalyst Pt-S / Mg3AlO prepared in Example 1 4.5 The conversion rate of the 300-hour long cycle reaction test. DETAILED DESCRIPTION

[0055] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] Unless otherwise specified, the various raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.

[0057] Example 1 This embodiment provides a dehydrogenation catalyst Pt-S / Mg3AlO 4.5 , and its preparation method comprises the following steps: 1. Preparation of carrier by sol-gel method Aluminum nitrate and magnesium nitrate with a molar ratio of magnesium to aluminum of 3:1 are dissolved in deionized water in turn, stirred and mixed evenly to obtain a mixed nitrate solution. A complexing agent citric acid is added to the mixed solution, and the added amount is controlled according to the molar ratio of the total metal ions of magnesium and aluminum to the complexing agent of 1:4 to prevent the hydrolysis of the metal ions and promote uniform dispersion.

[0058] 2. Conversion of sol to gel The sol solution was transferred to the evaporating flask of the rotary evaporator, with a rotation speed of 60 rpm, a water bath temperature of 60°C, and an air pressure of 0.02 MPa in the rotary evaporator. The solvent evaporated to form uniform bubbles that gradually evaporated until a uniform viscous gel was formed. At the same time, the color change of the solution was observed to stop the rotary evaporation step.

[0059] 3. Drying and Precursor Preparation The gel was transferred to a drying oven and dried at 80° C. for 18 hours to remove most of the water. After drying, a solid precursor of the dry gel was obtained, which was in powder form after grinding.

[0060] 4. Calcination of the carrier (two-step calcination): Take 100g of the precursor powder in a crucible and put it into a muffle furnace; use an air pump to continuously blow air into the muffle furnace at a gas rate of 1L / min; heat up to 350℃ at 5℃ / min and maintain for 4h; cool naturally to room temperature to obtain magnesium-aluminum composite oxide, which is taken out for use. Then put it into a tube furnace and calcine at 500℃ for 8h, and then take it out to obtain the carrier (preparation process see Figure 1 ).

[0061] 5. Ammonium sulfate modification of carrier surface A certain amount of carrier is placed in an evaporating flask of a rotary evaporator; 0.06 g / mL of ammonium sulfate aqueous solution is dripped onto the carrier through a burette according to the mass percentage of sulfur element 0.5% wt; the carrier after adding deionized water is placed in the evaporating flask of the rotary evaporator to completely evaporate the solvent; the above powder is calcined in a tubular furnace with an air flow rate of 1 L / min at 350°C for 2 hours; after natural cooling, an ammonium sulfate modified carrier is obtained.

[0062] 6. Impregnation of platinum active components: The sulfur-modified carrier was placed in the evaporation flask of the rotary evaporator; according to the target platinum mass fraction of 0.3%wt, a 0.01g / mL chloroplatinic acid aqueous solution was taken and dripped into the rotary evaporation flask through a burette, and the dry solution was rotary evaporated at 60°C and 0.02MPa; the carrier impregnated with platinum salt was further transferred to a tube furnace and calcined at 350°C for 4 h to obtain Pt-S / Mg3AlO 4.5 Catalyst (preparation process see Figure 2 ).

[0063] In the present invention, when the molar ratio of magnesium to aluminum in the carrier is 2:1, 2.5:1 and δ is other values ​​in the range of 4 to 6 except 4.5, the effect of the prepared dehydrogenation catalyst is equivalent to that of Example 1. At the same time, when the temperature of the primary calcination and the temperature of the secondary calcination are within the range defined by the present invention, the effect is equivalent to that of Example 1, because when within the above-defined range, a carrier having a synergistic structure of a layered hydrotalcite structure, a spinel structure, and a transitional mixed state structure close to a crystalline state can be obtained. Due to space limitations, no further description is given.

[0064] Comparative Example 1 This comparative example provides a dehydrogenation catalyst Pt / Mg3AlO 4.5 The preparation method thereof is different from that of Example 1 only in that step 5 is not included, i.e., the impregnation of the sulfur source is not performed.

[0065] Comparative Example 2 This comparative example provides a dehydrogenation catalyst Pt-S / Mg3AlO 4.5 The preparation method thereof is different from that of Example 1 only in that the catalyst carrier is commercially available hydrotalcite as a reference, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (CAS No.: 11097-59-9; molecular formula: Mg6Al2(CO3)(OH)16·4H2O; molecular weight: 603.98; MDL No.: MFCD01746913; PubChem No.: 159347; PubChem SID: 488188287), wherein the molar ratio of magnesium to aluminum is 3:1.

[0066] Comparative Example 3 This comparative example provides a dehydrogenation catalyst S-Pt / Mg3AlO 4.5 The preparation method thereof is different from that of Example 1 only in that the platinum salt is impregnated first and then the sulfur salt is impregnated.

[0067] Comparative Example 4 This comparative example provides a dehydrogenation catalyst Pt-S / Mg3AlO 4.5 The preparation method thereof is different from that of Example 1 only in that the carrier is prepared by coprecipitation method, and the specific preparation method comprises the following steps: 1. Prepare chloroplatinic acid solution: 1) Place chloroplatinic acid in a beaker and add a small amount of deionized water to dissolve it; 2) Use a dropper to transfer the solution in the beaker into a 100 ml brown volumetric flask; 3) Continue to add deionized water to make the volume to 100 ml to prepare a chloroplatinic acid aqueous solution; 4) Store in refrigerator away from light until ready for use.

[0068] 2. Prepare ammonium sulfate solution: 1) Place ammonium sulfate in a beaker and add a small amount of deionized water to dissolve it; 2) Use a dropper to transfer the solution in the beaker into a 100 ml brown volumetric flask; 3) Continue to add deionized water to make up to 100 ml to prepare an ammonium sulfate aqueous solution; 4) Place in the refrigerator and keep refrigerated for later use.

[0069] 3. Preparation of carrier by co-precipitation method: 1) Mg 2+ / A1 3+ The molar ratio of Mg(NO)2·6H2O is 3:1. 3.84 g Mg(NO)2·6H2O, 1.88 g Al(NO)3·9H2O, and 1.53 mL chloroplatinic acid acetone solution (concentration 0.01 g / mL) are weighed and added into 40 mL deionized water to obtain salt solution A.

[0070] 2) Weigh 2.4 g NaOH and 0.4 g Na2CO3 and dissolve them in 50 mL water to obtain alkaline solution B.

[0071] 3) Add solution A and solution B into the three-necked flask simultaneously while stirring, and control the pH of the suspension to around 9.8.

[0072] 4) After the addition of solution A is completed, continue to stir and react for 2 hours while maintaining the pH at about 9.8. Place the suspension obtained above in a hydrothermal autoclave and age at 95 °C for 10 hours.

[0073] 5) After aging, the mixture was cooled to room temperature and filtered. During the filtration process, the mixture was washed with water and alcohol for three times each. The filter cake obtained by filtration was vacuum dried at 60 °C to obtain magnesium aluminum hydrotalcite.

[0074] 6) Calcined magnesium aluminum hydrotalcite: (1) Put the synthetic hydrotalcite powder into a crucible and place it into a muffle furnace; (2) Calcination in a muffle furnace for 4 hours, heating to 350°C at a rate of 5°C / min; (3) After transferring to a tube furnace, the temperature was raised to 500°C at a rate of 5°C / min and calcined for 8 hours; (4) After naturally cooling to room temperature, magnesium-aluminum composite oxide is obtained.

[0075] 4. Impregnation of carrier surface active components 1) Add the above carrier into an eggplant-shaped flask; 2) Take the ammonium sulfate solution, mix it with the ionized water, and aspirate it into the burette; 3) Continuously shake the eggplant-shaped flask, and slowly drip the liquid in the burette into the eggplant-shaped flask to mix with the carrier, and continue to add deionized water; 4) Place the flask in a rotary evaporator and run for 30 minutes until the solution is completely evaporated, then place in a vacuum drying oven and dry for 2 hours; 5) Transfer the catalyst into a muffle furnace and heat it to 350°C at a rate of 5°C / min and calcine it for 2 hours to obtain a modified catalyst with a surface sulfur mass fraction of 0.5%wt; 6) Immersing in chloroplatinic acid aqueous solution in the same manner as above; 7) In the same manner as above, the mixture was placed in a muffle furnace and heated to 350° C. at a rate of 5° C. / min and calcined for 4 hours to obtain a platinum-impregnated platinum-sulfur surface-modified magnesium-aluminum mixed oxide catalyst.

[0076] Comparative Example 5 This comparative example provides a dehydrogenation catalyst Pt / Mg3AlO 4.5 The difference between the preparation method and Example 1 is that the catalyst carrier is commercially available hydrotalcite as a reference, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (CAS No.: 11097-59-9; molecular formula: Mg6Al2(CO3)(OH)16·4H2O; molecular weight: 603.98; MDL No.: MFCD01746913; PubChem No.: 159347; PubChem SID: 488188287), wherein the molar ratio of magnesium to aluminum is 3:1; and step 5 is not included, i.e., the impregnation of the sulfur source is not performed.

[0077] Comparative Example 6 This comparative example provides a dehydrogenation catalyst Pt / Mg3AlO 4.5 The difference between its preparation method and that of Example 1 is that the carrier is prepared by coprecipitation (the same as the method of Comparative Example 4), and step 5 is not included, that is, the impregnation of the sulfur source is not performed.

[0078] Test example 1. Characterization and testing of catalysts: The calcined catalyst can be characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), etc. to determine its structure and the dispersion of platinum particles.

[0079] Figure 3 The dehydrogenation catalyst Pt-S / Mg3AlO prepared in Example 1 of the present invention 4.5 The scanning transmission electron micrographs of the reaction, where A represents the 2nm image before the reaction and B represents the 2nm image after the reaction. It can be seen from the transmission electron micrographs that the Pt nanoparticles are in a cluster state before and after the reaction.

[0080] Figure 4 The dehydrogenation catalyst Pt / Mg3AlO prepared in Comparative Example 1 4.5The scanning transmission electron micrographs of the reaction, where A represents the 2nm image before the reaction and B represents the 2nm image after the reaction. It can be seen from the transmission electron micrographs that the Pt nanoparticles are in a cluster state before and after the reaction.

[0081] Figure 4 After the reaction, the size of the Pt clusters became significantly smaller and moved into the support. Figure 3 The Pt clusters loaded on the surface of the support modified by S maintain their size and relative position to the support surface. The modification of trace sulfur on the support surface enhances the interaction between the active metal clusters and the modified support, anchoring Pt on the surface.

[0082] The results show that the reconstruction of the support surface by S anchors the active Pt clusters, while the active Pt of the catalyst without S modification shows the behavior of Pt particles migrating into the support crystal during the reaction. This behavior can be attributed to the weak metal-support interaction, and the atoms of the Pt clusters gradually migrate to the inner layer of the support in the atmosphere of continuously generated hydrogen.

[0083] Figure 5 The dehydrogenation catalyst Pt-S / Mg3AlO prepared in Example 1 of the present invention 4.5 The X-ray diffraction pattern (XRD) of MgO shows that the characteristic peaks and the characteristic signals of magnesium-aluminum mixed oxides (hydrotalcite and spinel) are weakened, indicating that Mg3AlO 4.5 The sulfur (S) species first impregnated on the support surface significantly changed the surface structure of the freshly prepared catalyst.

[0084] Figure 6 The dehydrogenation catalyst Pt / Mg3AlO prepared in Comparative Example 1 of the present invention 4.5 The XRD crystal spectrum of the catalyst shows that the crystal signal of MgO is obvious, and more magnesium oxide substances are enriched on the surface. Combined with the performance of the chemical reaction conversion rate of Example 1 and Comparative Example 1, it confirms the positive effect of the addition of S sulfur substances on anchoring and stabilizing the Pt clusters on the surface of the magnesium-aluminum mixed oxide, and explains that the migration of Pt clusters into the carrier during the dehydrogenation process will reduce the dehydrogenation efficiency of methylcyclohexane. Therefore, adding S-containing additives to modify the surface of the modified carrier helps to anchor the Pt clusters to maintain a moderate micro-nano state, and explains that the Pt clusters on the magnesium-aluminum mixed oxide carrier are 0.2-0.5nm.

[0085] Figure 7 The oxygen 1s orbital energy level diagram (O1s orbital) of the X-ray photoelectron spectroscopy (XPS) is shown in Figure 1. The Pt / Mg3AlO 4.5 (Top) Pt-S / Mg3AlO with sulfur-modified support 4.5(below), the XPS O1s energy curve of the catalyst without S surface modification migrates to a lower binding energy, indicating that more lattice oxygen is generated. It can also be explained that the formation of lattice oxygen on the carrier surface causes the atoms of the active Pt noble metal clusters to gradually migrate into the lattice, thereby covering the active sites of Pt and resulting in excessively strong metal-carrier interactions, which limits the performance of the Pt active sites on the surface for catalytic dehydrogenation of methylcyclohexane. In summary, the doping of S substances on the carrier surface changes the crystal structure of MgO and magnesium-aluminum mixed oxides on the surface, while anchoring the Pt clusters with appropriate metal-carrier interactions, maintaining excellent stability and catalytic activity.

[0086] Figure 8 The results of the hydrogen temperature programmed reduction experiment (H2-TPR) of the catalysts of Example 1 and Comparative Example 1 are shown in the present invention. This experiment can reflect the degree of interaction between the metal on the catalyst surface and the carrier and the reduction properties during the temperature increase process. Figure 8 It can be seen that the first reduction peak of the mixed oxide modified by S on the support surface tends to the area below 300°C, and it occupies the most important peak area in the overall reduction temperature range, indicating that the interaction between the metal of the Pt cluster of the catalyst doped with S on the support surface and the magnesium-aluminum mixed oxide support has obviously migrated to a lower temperature range, which is strong evidence of the activity and stability of the methylcyclohexane dehydrogenation reaction. The first reduction main peak of the magnesium-aluminum mixed oxide catalyst not doped with S is located in the temperature range above 400°C, indicating that the activity of its Pt active metal cluster is weak, combined with Figure 7 The XPS results show that the catalyst without sulfur S has more surface lattice oxygen, which indicates that the phenomenon of less lattice oxygen after S doping promotes the catalytic activity and stability of Pt clusters.

[0087] Fig. 9The nitrogen isothermal adsorption-desorption curve (left) and pore size distribution curve (right) of the catalyst illustrated in Example 1 of the present invention. The principle of measuring specific surface area by gas adsorption method is based on the adsorption characteristics of gas on the solid surface. Under a certain pressure, the surface of the sample particles (adsorbent) under test has a reversible physical adsorption effect on gas molecules (adsorbates) at ultra-low temperature, and there is a certain equilibrium adsorption amount corresponding to a certain pressure. By measuring the equilibrium adsorption amount, the specific surface area of ​​the sample is equivalently calculated using a theoretical model. The nitrogen adsorption and desorption curves in the left figure basically coincide with each other, and the curve is concave because the interaction between the adsorbate molecules is stronger than that between the adsorbate and the adsorbent, and the adsorption heat of the first layer is smaller than the liquefaction heat of the adsorbate, so that the adsorbate is more difficult to adsorb in the initial stage of adsorption. As the adsorption process proceeds, the adsorption undergoes self-acceleration, and the number of adsorption layers is not limited. This phenomenon is between the adsorption and desorption curves of layered hydrotalcite and spinel. Combined with the examples in references (https: / / doi.org / 10.1016 / j.ceja.2022.100437. and https: / / doi.org / 10.1016 / j.jiec.2022.08.006), it can be seen that the microstructure of Example 1 is in a state where two mixed metal oxides coexist and are mainly in a mesoporous state.

[0088] Fig.10 The thermogravimetric analysis diagram of the catalyst prepared by the sol-gel / impregnation method of Example 1 and Comparative Example 1 of the present invention is shown. Fig.10 Thermogravimetric analysis (TG) curves of the two catalysts combined with the difference thermogravimetry (DTG) curves show that the addition of sulfur overall increases the weight decomposition temperature of the catalyst and effectively enhances the high temperature resistance of the catalyst.

[0089] 2. The dehydrogenation catalysts of the embodiments and comparative examples were subjected to a dehydrogenation reaction test, which specifically comprises the following steps: First, the dehydrogenation catalysts in the examples and comparative examples were subjected to reduction pretreatment: The catalyst was loaded into a fixed bed reactor and hydrogen was introduced at a hydrogen flow rate of 5 mL / min / gcat; the temperature was raised from room temperature to 150 °C at a rate of 5 °C / min and maintained for 2 h; then the temperature was raised to the reaction temperature of 250 °C at a rate of 5 °C / min and maintained for 2 h.

[0090] The pretreated catalyst is then subjected to a dehydrogenation reaction, which specifically comprises the following steps: When loading the catalyst, in order to prevent the catalyst from being carried into the pipeline by the gas during the reaction, an appropriate amount of quartz wool needs to be added to the bottom of the fixed bed reactor; tighten the nut at one end, add the prepared catalyst into the tubular reactor in sequence using a funnel, and then add a small amount of quartz wool to the upper layer of the catalyst, tighten the nut with the thermocouple at one end, and then install the reactor on the device.

[0091] Add the catalyst to the reaction tube, seal it and check the air tightness, open the hydrogen bottle and valve to adjust the hydrogen flow, use soapy water to check for liquid leakage, and after confirming that there is no error, adjust the valve to discharge hydrogen at a rate of about one to two bubbles per second. After stabilization, Fig.11 As shown in the figure, a temperature rising program is set to heat the catalyst to 200 °C at a heating rate of 5 °C / min, keep it at 200 °C for 120 min, then increase the temperature to 375 °C at a rate of 5 °C / min, keep it at this temperature for 120 min, and naturally cool it to room temperature under the condition of passing hydrogen to obtain the catalyst after hydrogen pretreatment.

[0092] Close the hydrogen cylinder, close the gas line, discharge the remaining hydrogen in the tube, and introduce nitrogen as a protective gas for purging. When all the hydrogen in the tube is discharged, stop introducing nitrogen. Fig.12 , set the temperature program to heat the catalyst to 350℃ at a heating rate of 5℃ / min, turn on the heating switches of the preheater and vaporization chamber, and set the temperature to 150℃, then turn on the micro-constant flow pump (time setting is infinite) at 0.1mL / min (space velocity: 0.445h -1 ) was introduced into the device at a feed rate of 1.5 1 / 2 ...

[0093] Finally, the collected products were analyzed on an Agilent 7890A gas chromatograph, and the quantitative method was the internal standard method (decane was the internal standard). The following formula is the calculation formula for the conversion rate of methylcyclohexane (MCH), the selectivity of toluene, and the hydrogen release rate of the reaction.

[0094] Where: u is the feed rate of MCH, mL / min; ρ is the density of MCH, g / mL; C is the conversion rate of MCH, %; mis the amount of catalyst used, g; M is the molar mass of MCH, g / mol; ω is the content of active component Pt, %.

[0095] The conversion results of the 300-hour long-cycle reaction test of the dehydrogenation catalysts prepared in the examples and comparative examples are shown in Table 1.

[0096] Table 1

[0097] Fig.13 The conversion rate of the dehydrogenation catalyst prepared in Example 1 was tested over a 300-hour long-cycle reaction. Fig.13 The reaction is shown over a long period of 300 hours at a conversion temperature of 350°C, which is the steady-state temperature of the reaction, with an average conversion rate of 95.7%.

[0098] The comparison between Example 1 and Comparative Examples 1-6 shows that the preparation route of preparing the magnesium-aluminum mixed oxide support by the sol-gel method in conjunction with first doping with sulfur and then impregnating with platinum is conducive to obtaining a high MCH dehydrogenation conversion rate. This is because the modification of the surface of the magnesium-aluminum mixed oxide support by sulfur enhances the metal-support interaction of anchoring Pt clusters, and the alkaline support surface enhances the ability to resist carbon deposition. In summary, the addition of sulfur enhances the interaction between platinum and the support, and inhibits the migration of trace Pt clusters into the support lattice. In addition, for catalysts not impregnated with sulfur, the sol-gel method of preparing the support is also significantly better than commercially available hydrotalcite and co-precipitation methods.

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A dehydrogenation catalyst, characterized in that The dehydrogenation catalyst uses sulfur-modified magnesium-aluminum mixed oxide as a carrier and Pt metal clusters as active centers; wherein the carrier is a mixed metal oxide having a layered hydrotalcite structure, a spinel structure and a near-crystalline synergistic structure.

2. The dehydrogenation catalyst according to claim 1, characterized in that The particle size of the Pt metal cluster is 0.2-0.5 nm.

3. The dehydrogenation catalyst according to claim 1 or 2, characterized in that The dehydrogenation catalyst is sulfur-modified Mg x Al y O δ is a vector, wherein x>y, δ represents any value between 4 and 6; preferably, x:y=(2-3):

1.

4. The dehydrogenation catalyst according to any one of claims 1 to 3, characterized in that The surface area of ​​the carrier is 100 m 2 / g or more, pore volume 0.50 cm 3 / g or more, and the pore diameter is 5nm or more.

5. The dehydrogenation catalyst according to any one of claims 1 to 4, characterized in that Based on the mass of the dehydrogenation catalyst, the content of the platinum metal clusters is 0.1wt%~0.8wt%.

6. The method for preparing the dehydrogenation catalyst according to any one of claims 1 to 5, characterized in that: include: S1: Mixing magnesium salt solution, aluminum salt solution and complexing agent to obtain sol solution; the molar ratio of magnesium and aluminum is (2-3):1; S2: heating the sol solution under reduced pressure on a rotary evaporator to obtain a gel, and then drying the gel to obtain a solid precursor of a xerogel, and grinding to obtain a precursor powder; S3: calcining the precursor powder in a muffle furnace at 300-400° C., and then calcining it in a tube furnace at 450-600° C. to obtain a carrier; S4: sequentially loading the sulfur source and the Pt clusters on the carrier by an impregnation method.

7. The method for preparing a dehydrogenation catalyst according to claim 5, characterized in that: The magnesium salt includes one or more of magnesium acetate, magnesium nitrate and magnesium chloride; And / or, the aluminum salt solution includes one or more of aluminum acetate, aluminum chloride and aluminum nitrate; and / or, the complexing agent comprises one or more of EDTA, citric acid, sodium citrate, ammonium citrate, maleic acid, glycine, ethanolamine, diethanolamine and triethanolamine; Preferably, the molar ratio of the two metal ions of magnesium and aluminum to the complexing agent is 1:(4-9).

8. The method for preparing a dehydrogenation catalyst according to claim 6, characterized in that: S1: Mixing magnesium salt solution, aluminum salt solution and complexing agent to obtain sol solution; the molar ratio of magnesium and aluminum is (2-3):1; S2: Rotary evaporating the sol solution at 40-90° C. to obtain a gel, and then drying the gel at 80-100° C. to obtain a solid precursor of a dry gel, and grinding to obtain a precursor powder; S3: calcining the precursor powder in a muffle furnace at 300-400° C. and then calcining it in a tube furnace at 450-600° C. to obtain a carrier; S4: impregnating the support in a sulfur salt solution, gently impregnating the support at 0.007-0.07 MPa and 40-90° C. in a rotary evaporator by reducing the pressure in the flask to control the boiling degree, and then calcining the support at 300-400° C. to obtain a sulfur-modified support; S5: impregnating the sulfur-modified support in a platinum salt solution, gently impregnating in a rotary evaporator at 0.007-0.07 MPa and 40-90° C. by reducing the pressure in the flask to control the boiling degree, and then calcining at 300-400° C.; Preferably, the sulfur salt includes one or more of ammonium sulfate, ammonium sulfite, ammonium bisulfate, ammonium thiosulfate, and ammonium sulfite; Preferably, the platinum salt includes one or more of chloroplatinic acid, ammonium chloroplatinate, platinum nitrate, platinum tetrachloride, platinum alkoxide, platinum oxide, platinum acetylacetonate and platinum carbonyl compound.

9. Use of the dehydrogenation catalyst according to any one of claims 1 to 4 or the dehydrogenation catalyst prepared by the preparation method according to any one of claims 5 to 8 in the dehydrogenation of cycloalkane; preferably, the cycloalkane is methylcyclohexane.

10. Use of the dehydrogenation catalyst according to claim 9 in the dehydrogenation of cycloalkanes, characterized in that: The dehydrogenation catalyst is pretreated before use, and the pretreatment includes subjecting the dehydrogenation catalyst to a reduction reaction in a hydrogen atmosphere at 150-250° C., and then cooling to 25-30° C.; preferably, the hydrogen flow rate is 2-8 mL / min / gcat.

Citation Information

Patent Citations

  • A platinum-tin supported hydrotalcite dehydrogenation catalyst, its preparation method and application

    CN107376907B

  • Hydrocarbon dehydrogenation catalyst as well as preparation method and application thereof

    CN109331823A

  • Monatomic catalyst doped with rare earth element and used for hydrogenation of organic hydrogen storage medium and preparation method of monatomic catalyst

    CN113070061A

  • Long-life low-platinum bimetallic catalyst for methylcyclohexane and preparation method of long-life low-platinum bimetallic catalyst

    CN114011431A

  • Platinum-based catalyst as well as preparation method and application thereof

    CN116851023A

Cited By

  • Pt cluster catalyst, preparation method and application

    CN120037905A

  • A Pt cluster catalyst, preparation method and application

    CN120037905B